Corrigendum: Family Support and Medication Adherence in Patients in Prolanis Program - Aini, Zahratul; Suardi, Hijra Novia; Dewi, Fitria Meutia; Ibrahim, Tilaili; Waraztuty, Ika; Mulia, Vera Dewi (Majalah Kedokteran Bandung, 2025)
This corrigendum refers to:  Family Support and Medication Adherence in Patients in Prolanis Program. Majalah Kedokteran Bandung. 2025;57(3):203–211. DOI: https://doi.org/10.15395/mkb.v57.4004